Electrolyte and silicon carbon battery

By using components such as bis(1,2-cycloglyceride)oxalate, tetraethoxysilane and bis(trimethylsilyl)sulfate in the electrolyte, reacting with the negative electrode surface of the silicon carbon battery to form a cross polymerization network, the problem of poor storage stability of silicon carbon batteries at high temperatures is solved, and the cycling performance and high temperature storage performance of the battery are significantly improved.

CN119764339AActive Publication Date: 2025-04-04EVE ENERGY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411963757.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The problem of poor storage stability of silicon-carbon batteries at high temperatures is that existing additives cannot meet the needs of long cycle and wide temperature working environments.

Method used

An electrolyte is provided, which contains 0.1 to 3% bis(1,2-cycloglyceride) oxalate, 0.1 to 3% tetraethoxysilane, 0.1 to 3% bis(trimethylsilyl) sulfate, and a residual amount of organic solvent and lithium salt. The reaction of these components with the surface of silicon carbon negative electrodes forms a cross polymerization network to improve the mechanical strength and flexibility of the SEI film.

Benefits of technology

The cycling performance and high-temperature storage performance of the battery are improved, the charged interface is stabilized, and the SEI film with high conductivity and high thermal stability is formed, extending the cycling life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218858150000051
    Figure BDA0005218858150000051
  • Figure BDA0005218858150000061
    Figure BDA0005218858150000061
  • Figure BDA0005218858150000081
    Figure BDA0005218858150000081
Patent Text Reader

Abstract

The invention provides an electrolyte and a silicon-carbon battery. The electrolyte is prepared from the following components in percentage by mass: 0.1 to 3 percent of bis (1, 2-cyclosulfurous acid glyceride) oxalate, 0.1 to 3 percent of tetraethoxysilane, 0.1 to 3 percent of bis (trimethylsilyl) sulfate and the balance of organic solvent and lithium salt. Tetraethoxysilane and bis (trimethylsilyl) sulfate in the electrolyte can easily react with natural silanol groups on the surface of a silicon-carbon negative electrode, a cross polymerization network of Si-O-Si bonds is formed on the surface of the negative electrode, the mechanical strength and flexibility of an SEI film can be improved, a charged interface can be stabilized, and the electrochemical performance of the battery can be improved; bis (1, 2-cyclosulfurous acid glyceride) oxalate and bis (trimethylsilyl) sulfate are combined, and a protection layer with a three-dimensional network can be formed on the anode of the battery under the synergistic effect of the two, so that various properties of the battery can be balanced, and the cycle performance and the high-temperature storage performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte and a silicon-carbon battery. Background Art

[0002] Negative electrode materials with high specific capacity are an important breakthrough in improving the energy density of lithium-ion batteries. Compared with graphite negative electrodes, silicon-carbon negative electrodes have obvious advantages in compaction density and specific capacity. It is difficult to significantly improve graphite negative electrode materials, and the theoretical energy density of 372mAh / g is far from the theoretical energy density of silicon negative electrode materials as high as 4200mAh / g. Silicon negative electrode materials have suitable discharge potentials and relatively abundant reserves in nature. They are considered to be the most likely negative electrode materials to replace graphite.

[0003] However, there are many problems in the commercial application of single silicon in lithium-ion batteries. On the one hand, internal stress will be generated in the process of lithium ion deintercalation and embedding in silicon materials, which will cause volume expansion and damage to the material structure, and may lead to the rupture of active particles, pulverization of pole pieces and shedding of active materials. On the other hand, due to the change in silicon volume, the solid electrolyte interface film (SEI) will rupture, and the newly exposed silicon on the surface will produce a new SEI film, while continuously consuming lithium ions in the electrolyte, reducing the initial coulomb efficiency. Finally, during the cycle, due to the volume change of the electrode material, the SEI film at the silicon negative electrode interface will grow and rupture repeatedly, and the lithium source will be quickly consumed. A series of problems together lead to rapid capacity decay, which greatly affects the cycle stability.

[0004] Classic film-forming additives such as fluoroethylene carbonate (FEC), vinylene carbonate (VC), propylene sulfite (PS), dithiothreitol sulfate (DTD) etc. play an important role in lithium-ion batteries. However, with the increase of silicon doping ratio and the continuous development of high-voltage materials, conventional additives cannot meet the requirements of long-cycle and wide-temperature working environment. From the current commercial application, DTD can significantly improve the high-temperature storage and high-temperature cycle performance of batteries, and is the most effective additive among sulfate compounds. However, DTD is relatively expensive, and its low-temperature storage requirement brings inconvenience to the transportation and storage of electrolytes. After VC film is formed, there are oxidation stability problems in high-temperature and high-voltage systems, which leads to a series of side decompositions. Although PS performs well in inhibiting gas production, it is easy to continuously oxidize with the positive electrode, increase the membrane impedance, and have problems such as rapid growth of direct current internal resistance (DCR) in long cycles. PS also has defects such as great harm to the body. Summary of the invention

[0005] The main purpose of the present application is to provide an electrolyte and a silicon-carbon battery to solve the problem of poor high-temperature storage stability of silicon-carbon batteries in the prior art.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present application, an electrolyte is provided, which comprises, by mass percentage: 0.1-3% of bis(1,2-cyclosulfite glyceryl) oxalate, 0.1-3% of tetraethoxysilane, 0.1-3% of bis(trimethylsilyl) sulfate, and the remainder of organic solvent and lithium salt.

[0007] Furthermore, the mass content of the above-mentioned bis(1,2-cyclosulfite glyceryl) oxalate is 0.3-3%; and / or the mass content of tetraethoxysilane is 0.3-3%; and / or the mass content of bis(trimethylsilyl) sulfate is 0.5-3%.

[0008] Furthermore, the mass ratio of the above-mentioned bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate is (0.3-1):(0.3-1):(0.5-1).

[0009] Furthermore, the electrolyte further comprises 1.1 to 18% of an additive; further, the additive is selected from any one or more of fluoroethylene carbonate, succinonitrile, adiponitrile, glutaronitrile, 1,3,6-hexanetrinitrile, vinylene carbonate and vinyl ethylene carbonate.

[0010] Furthermore, the additive is a combination of fluoroethylene carbonate and succinonitrile, and the mass ratio of fluoroethylene carbonate to succinonitrile is (5-15):(0.1-1).

[0011] Furthermore, the mass content of the above-mentioned lithium salt is 10-27%; further, the lithium salt is selected from any one or more of LiPF6, lithium difluorooxalatoborate, LiPO2F2, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.

[0012] Furthermore, the above-mentioned lithium salt is a combination of LiPF6, lithium difluorooxalatoborate and LiPO2F2, and the mass ratio of LiPF6, lithium difluorooxalatoborate and LiPO2F2 is (10-14):(1-5):(0.5-5).

[0013] Furthermore, the organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, butylene carbonate, ethyl propionate, ethyl acetate and propyl propionate.

[0014] Furthermore, the above-mentioned organic solvent is a combination of ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl propionate, and the mass ratio of ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl propionate is (5-15):(15-25):(10-45):(15-60).

[0015] According to another aspect of the present application, a silicon-carbon battery is provided, comprising a positive electrode sheet, an electrolyte and a silicon-carbon negative electrode sheet, wherein the electrolyte is the aforementioned electrolyte.

[0016] By applying the technical solution of the present application, tetraethoxysilane and bis(trimethylsilyl) sulfate in the electrolyte of the present application are easy to react with the natural silanol groups on the surface of the silicon-carbon negative electrode to form a cross-polymer network of Si-O-Si bonds on the surface of the negative electrode, which helps to improve the mechanical strength and flexibility of the SEI film, thereby stabilizing the charged interface and improving the electrochemical performance of the battery. Otherwise, Li + It will react with silanol to generate Li2O and LiOH; bis(1,2-cyclosulfite glyceryl) oxalate and bis(trimethylsilyl) sulfate combine to form sulfur-containing compounds of the positive electrode protective film on the one hand, and on the other hand, it helps to inhibit the further decomposition of the SEI of the organic polymer, and plays a role in modifying the SEI. The synergistic effect of the two can form a protective layer with a three-dimensional network on the anode of the battery, and provide a cross-linked protective layer to form a SEI with high conductivity and high thermal stability, which helps to balance the various performances of the battery, thereby helping to improve the battery's cycle performance and high-temperature storage performance. Controlling the mass content of bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate in the electrolyte within the above range helps to further improve the synergistic effect between the three, thereby helping to further improve the battery's cycle performance and high-temperature storage performance. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.

[0018] As analyzed in the background technology of the present application, the silicon-carbon battery in the prior art has the problem of poor high-temperature storage stability. In order to solve this problem, the present application provides an electrolyte and a silicon-carbon battery.

[0019] In a typical embodiment of the present application, an electrolyte is provided, which includes, by mass percentage, 0.1-3% of bis(1,2-cyclosulfite glyceryl) oxalate, 0.1-3% of tetraethoxysilane, 0.1-3% of bis(trimethylsilyl) sulfate, and the remainder of an organic solvent and a lithium salt.

[0020] The tetraethoxysilane and bis(trimethylsilyl) sulfate in the electrolyte of the present invention are easy to react with the natural silanol groups on the surface of the silicon-carbon negative electrode to form a cross-polymer network of Si-O-Si bonds on the surface of the negative electrode, which helps to improve the mechanical strength and flexibility of the SEI film, thereby stabilizing the charged interface and improving the electrochemical performance of the battery. Otherwise, Li+ It will react with silanol to generate Li2O and LiOH; bis(1,2-cyclosulfite glyceryl) oxalate and bis(trimethylsilyl) sulfate combine to form sulfur-containing compounds of the positive electrode protective film on the one hand, and on the other hand, it helps to inhibit the further decomposition of the SEI of the organic polymer, and plays a role in modifying the SEI. The synergistic effect of the two can form a protective layer with a three-dimensional network on the anode of the battery, and provide a cross-linked protective layer to form a SEI with high conductivity and high thermal stability, which helps to balance the various performances of the battery, thereby helping to improve the battery's cycle performance and high-temperature storage performance. Controlling the mass content of bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate in the electrolyte within the above range helps to further improve the synergistic effect between the three, thereby helping to further improve the battery's cycle performance and high-temperature storage performance.

[0021] In one embodiment of the present application, the mass content of the above-mentioned bis(1,2-cyclosulfite glyceryl) oxalate is 0.3-3%; and / or, the mass content of tetraethoxysilane is 0.3-3%; and / or, the mass content of bis(trimethylsilyl) sulfate is 0.5-3%.

[0022] Controlling the mass content of bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate within the above range helps to further improve the mechanical strength and flexibility of the SEI film and inhibit further decomposition of the SEI of the organic polymer, thereby helping to improve the cycle performance and high-temperature storage performance of the battery.

[0023] In one embodiment of the present application, the mass ratio of the above-mentioned bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate is (0.3-1):(0.3-1):(0.5-1).

[0024] Controlling the mass ratio of bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate within the above range helps to further optimize the SEI film and inhibit the occurrence of side reactions, thereby helping to improve the cycle performance and high-temperature storage performance of the battery.

[0025] In one embodiment of the present application, the above-mentioned electrolyte also includes 1.1 to 18% of an additive; in one embodiment of the present application, the additive is selected from any one or more of fluoroethylene carbonate, succinonitrile, adiponitrile, glutaronitrile, 1,3,6-hexanetrinitrile, vinylene carbonate and vinyl ethylene carbonate.

[0026] The addition of additives helps to further optimize the performance of the SEI film, improve the battery's cycle stability, high temperature adaptability and first coulombic efficiency, while reducing gas production and expansion.

[0027] In one embodiment of the present application, the additive is a combination of fluoroethylene carbonate and succinonitrile, and the mass ratio of fluoroethylene carbonate to succinonitrile is (5-15):(0.1-1).

[0028] The addition of fluoroethylene carbonate can effectively improve the stability of the SEI film of the silicon-based negative electrode, especially under high voltage and wide temperature range conditions. The decomposition of fluoroethylene carbonate on the electrode surface can form a fluorine-rich SEI film, which has better electronic insulation, ionic conductivity and thermal stability, and can effectively inhibit the side reactions of the electrode material during the charge and discharge process, thereby extending the cycle life of the battery. The addition of succinonitrile helps to promote the dynamic balance of the SEI film during the battery charge and discharge process, reduce the rupture and regeneration of the film, thereby reducing the internal resistance of the battery and improving the cycle performance of the battery. The addition of succinonitrile can maintain good stability and continuity of the SEI film during the cycle, reduce the loss of active substances, and optimize the coulombic efficiency of the battery. Controlling the mass ratio of fluoroethylene carbonate and succinonitrile within the above range helps to improve the synergistic effect between the two, thereby helping to further improve the cycle performance and high-temperature storage performance of the battery.

[0029] In one embodiment of the present application, the mass content of the above-mentioned lithium salt is 10-27%; in one embodiment of the present application, the lithium salt is selected from any one or more of lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiODFB), LiPO2F2, lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0030] Lithium salt is the main source of lithium ions in the electrolyte. Controlling the mass content of lithium salt within the above range helps to make the electrolyte have good conductivity, improve the ion transmission efficiency, improve the chemical stability of the electrolyte, and reduce the generation of lithium precipitation and side reactions. Controlling the type of lithium salt within the above range helps to further improve the conductivity and stability of the electrolyte.

[0031] In one embodiment of the present application, the above-mentioned lithium salt is a combination of LiPF6, lithium difluorooxalatoborate and LiPO2F2, and the mass ratio of LiPF6, lithium difluorooxalatoborate and LiPO2F2 is (10-14):(1-5):(0.5-5).

[0032] The addition of LiPF6 helps to improve the conductivity and electrochemical stability of the electrolyte. Lithium difluorooxalatoborate and LiPO2F2 can participate in the formation of the SEI film and optimize the composition and structure of the SEI film. Lithium difluorooxalatoborate can promote the formation of a stable SEI film under high temperature conditions, while LiPO2F2 helps to form a fluorine-rich SEI film, improve the thermal stability and mechanical strength of the film, and reduce the volume change of the electrode during the charge and discharge process, thereby helping to improve the cycle stability and energy efficiency of the battery. Controlling the mass ratio of LiPF6, lithium difluorooxalatoborate and LiPO2F2 within the above range helps to give full play to the synergistic effect between the three, thereby helping to improve the conductivity of the electrolyte, the electrochemical window and the performance of the SEI film, thereby helping to improve the cycle stability, energy efficiency, wide temperature adaptability and overall safety of the battery.

[0033] In order to further improve the chemical stability of the electrolyte, in one embodiment of the present application, the above-mentioned organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, butylene carbonate, ethyl propionate, ethyl acetate and propyl propionate.

[0034] In one embodiment of the present application, the above-mentioned organic solvent is a combination of ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl propionate, and the mass ratio of ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl propionate is (5-15):(15-25):(10-45):(15-60).

[0035] Controlling the mass ratio of ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl propionate within the above range helps to give full play to the synergistic effect between the components, thereby helping to improve the conductivity and stability of the electrolyte.

[0036] In one embodiment of the present application, the electrolyte comprises, by mass percentage, 14% LiPF6, 1% lithium difluorooxalatoborate, 0.5% LiPO2F2, 5% fluoroethylene carbonate, 1% succinonitrile, 0.3% bis(1,2-cyclosulfite glyceryl) oxalate, 0.3% tetraethoxysilane, 0.5% bis(trimethylsilyl) sulfate and the remainder of an organic solvent, wherein the organic solvent is a combination of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl propionate (EP), and the mass ratio of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl propionate (EP) is 10:20:15:55.

[0037] In one embodiment of the present application, the electrolyte comprises, by mass percentage, 10% LiPF6, 5% lithium difluorooxalatoborate, 5% LiPO2F2, 15% fluoroethylene carbonate, 0.1% succinonitrile, 0.5% bis(1,2-cyclosulfite glyceryl) oxalate, 0.3% tetraethoxysilane, 0.5% bis(trimethylsilyl) sulfate and the remainder of an organic solvent, wherein the organic solvent is a combination of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl propionate (EP), and the mass ratio of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl propionate (EP) is 10:20:15:55.

[0038] In another typical embodiment of the present application, a silicon-carbon battery is provided, comprising a positive electrode sheet, an electrolyte and a silicon-carbon negative electrode sheet, wherein the electrolyte is the aforementioned electrolyte.

[0039] Since the above battery contains the electrolyte of the present application, the battery has good cycle stability and high-temperature storage performance.

[0040] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0041] Examples 1 to 14, Comparative Examples 1 to 4

[0042] In a glove box filled with nitrogen / argon (H2O < 0.5ppm), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) were mixed in a mass ratio of 10:20:15:55 to obtain an organic solvent, and then LiPF6, lithium difluorooxalatoborate, LiPO2F2, fluoroethylene carbonate and succinonitrile were slowly added to the organic solvent, and finally bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate were added, and the electrolyte was obtained after stirring evenly. In terms of mass percentage, the mass content of LiPF6 in the electrolyte is 14%, the mass content of lithium difluorooxalatoborate is 1%, the mass content of LiPO2F2 is 0.5%, the mass content of fluoroethylene carbonate is 5%, the mass content of succinonitrile is 1%, the mass contents of bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate are shown in Table 1, and the balance is organic solvent.

[0043] Table 1

[0044]

[0045]

[0046] Embodiment 15

[0047] The difference from Example 1 is that the mass content of fluoroethylene carbonate is 15%, the mass content of succinonitrile is 0.1%, and finally an electrolyte is obtained.

[0048] Example 16

[0049] The difference from Example 1 is that the mass content of fluoroethylene carbonate is 4%, and the mass content of succinonitrile is 2%, and finally an electrolyte is obtained.

[0050] Embodiment 17

[0051] The difference from Example 1 is that the mass content of LiPF6 is 10%, the mass content of lithium difluorooxalatoborate is 5%, and the mass content of LiPO2F2 is 5%, and finally an electrolyte is obtained.

[0052] Embodiment 18

[0053] The difference from Example 1 is that the mass content of LiPF6 is 17%, the mass content of lithium difluorooxalatoborate is 1%, and the mass content of LiPO2F2 is 0.5%, and finally an electrolyte is obtained.

[0054] Embodiment 19

[0055] The difference from Example 1 is that the mass ratio of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl propionate (EP) is 5:25:10:60 to finally obtain the electrolyte.

[0056] Embodiment 20

[0057] The difference from Example 1 is that the mass ratio of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl propionate (EP) is 4:26:9:61, and the electrolyte is finally obtained.

[0058] Comparative Example 5

[0059] The difference from Example 1 is that vinylene carbonate is used to replace bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate, and finally an electrolyte is obtained.

[0060] Preparation of the positive electrode: The positive electrode active materials lithium cobalt oxide (LCO), carbon nanotubes (CNT), conductive carbon black SP, and polyvinylidene fluoride (PVDF) are fully stirred and mixed in a mass ratio of 98:0.5:0.5:1.0, coated on aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.

[0061] Preparation of negative electrode: Silicon carbon negative electrode material (SiC), conductive carbon black (SP), single-walled carbon nanotubes (SWCNT) and binder polyacrylic acid (PAA) are mixed in a mass ratio of 80:9:1:10 and added to solvent deionized water. After mixing evenly, the mixture is coated on copper foil, dried and cold pressed to obtain a negative electrode sheet.

[0062] Preparation of battery: The positive electrode sheet, negative electrode sheet and separator prepared above are wound into a square battery cell, packaged with a polymer, and filled with the electrolyte prepared in the above examples and comparative examples.

[0063] Electrical performance test

[0064] Cycle performance test: At 25℃ or 45℃, the lithium-ion battery is charged to 4.5V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and left to stand for 10 minutes. Then, the lithium-ion battery is discharged to 3.0V at a constant current rate of 1C, and left to stand for 10 minutes. This is a charge and discharge cycle. The capacity retention rate (%) of the lithium-ion battery after N cycles = (discharge capacity of the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0065] High temperature storage performance test: First, charge and discharge the formed battery at 1.0C to 3.0V at room temperature, and record the initial thickness; charge at 0.2C constant current and constant voltage to 4.5V, and cut off at 0.02C; discharge at 0.2C constant current to 3.0V; as the initial capacity; charge at 0.2C constant current and constant voltage to 4.5V, and cut off at 0.02C; place the battery in a 60℃ constant temperature box for 14 days, then take out the battery, measure the hot thickness (record the hot thickness in the temperature box), leave it for 2h, discharge it at 0.2C constant current to 3.0V, and record it as the residual capacity; charge at 0.2C constant current and constant voltage to 4.5V, and cut off at 0.02C; leave it for 10min; discharge it at 0.2C constant current to 3.0V; record the recovery capacity.

[0066] After 14 days of storage at 60°C, the thermal thickness expansion rate of the battery = (thermal thickness - initial thickness) / initial thickness * 100% After 14 days of storage at 60°C, the battery capacity retention rate = (residual capacity / initial capacity) * 100%

[0067] Battery capacity recovery rate after 14 days storage at 60°C = (recovery capacity / initial capacity)*100%

[0068] The results of the cycle performance test and high temperature storage performance test of the above battery are shown in Table 2.

[0069] Table 2

[0070]

[0071] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:

[0072] The tetraethoxysilane and bis(trimethylsilyl) sulfate in the electrolyte of the present invention are easy to react with the natural silanol groups on the surface of the silicon-carbon negative electrode to form a cross-polymer network of Si-O-Si bonds on the surface of the negative electrode, which helps to improve the mechanical strength and flexibility of the SEI film, thereby stabilizing the charged interface and improving the electrochemical performance of the battery. Otherwise, Li + It will react with silanol to generate Li2O and LiOH; bis(1,2-cyclosulfite glyceryl) oxalate and bis(trimethylsilyl) sulfate combine to form sulfur-containing compounds of the positive electrode protective film on the one hand, and on the other hand, it helps to inhibit the further decomposition of the SEI of the organic polymer, and plays a role in modifying the SEI. The synergistic effect of the two can form a protective layer with a three-dimensional network on the anode of the battery, and provide a cross-linked protective layer to form a SEI with high conductivity and high thermal stability, which helps to balance the various performances of the battery, thereby helping to improve the battery's cycle performance and high-temperature storage performance. Controlling the mass content of bis(1,2-cyclosulfite glyceryl) oxalate, tetraethoxysilane and bis(trimethylsilyl) sulfate in the electrolyte within the above range helps to further improve the synergistic effect between the three, thereby helping to further improve the battery's cycle performance and high-temperature storage performance.

[0073] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An electrolyte, characterized in that: In terms of mass percentage, the electrolyte includes: 0.1-3% of bis(1,2-cyclosulfite glyceryl) oxalate, 0.1-3% of tetraethoxysilane, 0.1-3% of bis(trimethylsilyl) sulfate, and the remainder of organic solvent and lithium salt.

2. The electrolyte according to claim 1, characterized in that The mass content of the bis(1,2-cyclosulfite glyceryl) oxalate is 0.3-3%; and / or the mass content of the tetraethoxysilane is 0.3-3%; and / or the mass content of the bis(trimethylsilyl) sulfate is 0.5-3%.

3. The electrolyte according to claim 1 or 2, characterized in that The mass ratio of the bis(1,2-cyclosulfite glyceryl) oxalate, the tetraethoxysilane and the bis(trimethylsilyl) sulfate is (0.3-1):(0.3-1):(0.5-1).

4. The electrolyte according to any one of claims 1 to 3, characterized in that The electrolyte further comprises 1.1 to 18% of an additive; preferably, the additive is selected from any one or more of fluoroethylene carbonate, succinonitrile, adiponitrile, glutaronitrile, 1,3,6-hexanetrinitrile, vinylene carbonate and vinyl ethylene carbonate.

5. The electrolyte according to claim 4, characterized in that The additive is a combination of the fluoroethylene carbonate and the succinonitrile, and the mass ratio of the fluoroethylene carbonate to the succinonitrile is (5-15):(0.1-1).

6. The electrolyte according to any one of claims 1 to 5, characterized in that The mass content of the lithium salt is 10-27%; preferably, the lithium salt is selected from any one or more of LiPF6, lithium difluorooxalatoborate, LiPO2F2, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.

7. The electrolyte according to claim 6, characterized in that The lithium salt is a combination of the LiPF6, the lithium difluorooxalatoborate and the LiPO2F2, and the mass ratio of the LiPF6, the lithium difluorooxalatoborate and the LiPO2F2 is (10-14):(1-5):(0.5-5).

8. The electrolyte according to any one of claims 1 to 7, characterized in that The organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, butylene carbonate, ethyl propionate, ethyl acetate and propyl propionate.

9. The electrolyte according to claim 8, characterized in that The organic solvent is a combination of the ethylene carbonate, the propylene carbonate, the diethyl carbonate and the ethyl propionate, and the mass ratio of the ethylene carbonate, the propylene carbonate, the diethyl carbonate and the ethyl propionate is (5-15):(15-25):(10-45):(15-60).

10. A silicon-carbon battery, comprising a positive electrode sheet, an electrolyte and a silicon-carbon negative electrode sheet, characterized in that: The electrolyte is the electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery and electrolyte thereof

    CN103346349A

  • Sulfurous acid glyceride compound-based electrolyte additive and lithium ion battery

    CN105514484A

  • Electrolyte and secondary battery

    CN108242567A

  • Non-aqueous electrolyte and lithium ion secondary battery

    CN111048830A

  • 1,2- cyclic sulfite glycerol additive and lithium ion battery electrolyte containing same

    CN111668545A